Implementasi metode penugasan dalam optimalisasi motivasi belajar peserta didik pada pembelajaran daring kelas IV SD - Dinar Mahardhika Pratiwi; Hadi Mulyono; Fadhil Purnama Adi (Didaktika Dwija Indria, 2022)
The aim of this study are to analyse and describe the effects of learning method using, factors that affect student learning motivation, and the teacher’s effort to handle student with lower learning motivation. qualitative descriptive used in this research methods. Subject for this research are the teacher of fourth grader and the student of fourth grader SD N Totosari. Observation, interview, questionnaire, and document study are used for data collection technics in this research. Data validity used in this research. Miles and Huberman’s analysis used for data analysis. This study procedure using study case model by Creswell. The results of this research are knowing that the learning method is giving assignment to the students and this learning method affect the student’s learning motivation. Then, there are internal and external factors that affect the student’s learning motivation and the level of student’s learning motivation levelled as low. The next result is teacher’s effort to handle the lower learning motivation of the student are always following up the student, asked the students if they had any question, and etc.Kata kunci: learning method, learning motivation, online learning.